1996
DOI: 10.1021/jp960674p
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Laser-Ablated Iron Atoms with N2O, NO, and O2 in Condensing Nitrogen. Infrared Spectra and Density Functional Calculations of Ternary Iron Nitride Oxide Molecules

Abstract: Reactions of laser-ablated Fe atoms with N 2 O, NO, and O 2 in excess N 2 during condensation at 10 K produced new absorptions with 15 N and 18 O shifts that are assigned to the new ternary iron nitride oxide molecules NFeO, NFeO 2 , and N 2 FeO. DFT calculations of structure and isotopic frequencies support these assignments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(59 citation statements)
references
References 20 publications
(87 reference statements)
7
47
5
Order By: Relevance
“…The four lowest lying states are dominated by single configurations. Our results agree with previous works on FeN [3][4][5][6][7], and support the attribution that the ground state is indeed the 2 D with the 4 P state only 0.06 eV higher in energy. All values in cm À1 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The four lowest lying states are dominated by single configurations. Our results agree with previous works on FeN [3][4][5][6][7], and support the attribution that the ground state is indeed the 2 D with the 4 P state only 0.06 eV higher in energy. All values in cm À1 .…”
Section: Discussionsupporting
confidence: 93%
“…In doing so, the spin-orbit components 4 P 5/2 and 4 P 3/2 lie 811 and 1223 cm À1 above the ground state and are tentatively assigned as states b and c. Symmetry analysis of the DF bands also indicated that states b and c should have a different symmetry from the ground state. It was suggested that state a should also be a spin-orbit component of 4 P, in spite of the fact that its vibrational progression does not appear in the same bands where b and c progressions do and that no theoretical level nearer the ground state was left to account for it (a low-lying 6 R þ state was discarded by symmetry reasons). When we include the same splitting estimates in our MR-SDCI results, we end up with spin-orbit components of the 4 P state 215, 627, 1039, and 1451 cm À1 above the 2 D 5/2 state.…”
Section: Discussion On the Ordering Of Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…Formation of [FeOH(H 2 O)] + would give an ion with a calculated m/z of 90.9481, and, indeed, this ion was experimentally observed at m/z 90.9483. Andrews and coworkers have studied the reactions of laser‐ablated iron atoms, establishing that iron and its oxides react with N 2 8–10. They reported the formation of the pyramidal iron dinitride oxide, [N 2 FeO], demonstrating that the observed and calculated infrared bands matched well.…”
Section: Resultsmentioning
confidence: 93%
“…They reported the formation of the pyramidal iron dinitride oxide, [N 2 FeO], demonstrating that the observed and calculated infrared bands matched well. They also documented that the FeN bond is relatively strong 9. Betley and Peters later showed that an iron nitride could be reduced to ammonia at room temperature 11…”
Section: Resultsmentioning
confidence: 99%